Suppressing Nickel Oxide/Perovskite Interface Redox Reaction and Defects for Highly Performed and Stable Inverted Perovskite Solar Cells. Issue 10 (20th September 2022) - Ahmad, Sajjad; Ma, Ruiman; Zheng, Jiawei; Gary Kwok, Cheuk Kai; Zhou, Qisen; Ren, Zhenwei; Kim, Jinwook; He, Xinjun; Zhang, Xiaoliang; Yu, Kin Man; Choy, Wallace C. H.
Abstract: The inorganic hole transport layer of nickel oxide (NiO x ) has shown highly efficient, low‐cost, and scalable in perovskite photovoltaics. However, redox reactions at the interface between NiO x and perovskites limit their commercialization. In this study, ABABr (4‐(2‐Aminoethyl) benzoic acid bromide) between the NiO x and different perovskite layers to address the issues has been introduced. How the ABABr interacts with NiO x and perovskites is experimentally and theoretically investigated. These results show that the ABABr molecule chemically reacts with the NiO x via electrostatic attraction on one side, whereas on the other side, it forms a strong hydrogen bond via the NH3 + group with perovskites layers, thus directly diminishing the redox reaction between the NiO x and perovskites layers and passivating the layer surfaces. Additionally, the ABABr interface modification leads to significant improvements in perovskite film morphology, crystallization, and band alignment. The perovskites solar cells (PSCs) based on an ABABr interface modification show power conversion efficiency (PCE) improvement by over 13% and maintain over 90% of its PCE after continuous operation at maximum power point for over 500 h. The work not only contributes to the development of novel interlayers for stable PSCs but also to the understanding of how to prevent interface redox reactions. Abstract : A novel interface layer of ABABr (4‐(2‐Aminoethyl) benzoic acid bromide) is developed to suppress the redox reaction at the interface between the NiO x and different perovskites. An ABABr interface modification increases power conversion efficiency (PCE) by over 13% and the device maintains over 90% of its PCE after over 500 hours of continuous operation at maximum power point.